Morphometry-Based Identification of Tick Species Infecting Rabbits at the Agriculture and Forestry University Livestock Farm - Chaudhary, Min Kumar; Pathak, Chet Raj (Journal of Agriculture and Forestry University, 2025)
Rabbits (Oryctolagus cuniculus) are valuable as laboratory animals and farm assets due to their adaptability and rapid reproduction. They can host ticks that feed on blood and transmit various pathogens. Ticks and blood samples were collected from the AFU livestock farm from September 2023 to December 2023. The size of morphologic features was recorded, and the species was identified using taxonomic keys. An automatic hematology analyzer was used for hematological analysis of blood samples. A Giemsa-stained blood smear was observed with 1000x magnification using a binocular compound microscope for haemoparasites. About 32 tick specimens were collected from 16 rabbits, comprising 37.50% adult males, 25.00% adult females, 25.00% larvae, and 12.50% nymphs. All adults and nymphs were identified as Haemaphysalis howletti. The rabbits had a higher prevalence of ticks during early autumn (100%) than in late autumn (0%). There was a significant decrease in Total Erythrocyte Count (TEC), Hemoglobin (HGB), Hematocrit (HCT), and Platelet count (PLT), whereas an increase in Total Leucocyte Count (TLC) and granulocyte count occurred during the tick-infested state in rabbits (P<0.05). In addition, the overall prevalence of Anaplasma spp. was 31.25% in rabbits. Here, tick infestation showed a major role in hematological alterations and reservoirs for tick-borne pathogens. Thus, ultimately affects the health of rabbits, adding potential risk of zoonosis, and a challenge to public health.